2013
DOI: 10.5539/gjhs.v6n2p189
|View full text |Cite
|
Sign up to set email alerts
|

Betel Nut Usage Is a Major Risk Factor for Coronary Artery Disease

Abstract: Aim:The objective of our study was to assess betel nut usage as one of the major risk factors associated with coronary artery disease.Methods:This case control study consisted of 300 controls and 300 cases. A structured questionnaire was administered to the participants to assess consumption of betel nut and confounding variables. A respondent was considered a regular consumer of betel nut if he/she consumed one or more pieces of betel nut every day for a period of greater than 6 months.Results:About 8 in 10 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Its use generates euphoria 3 among users that contributes to widespread use; however, it has an array of negative effects including but not limited to oral, esophageal, and hepatocellular carcinoma, metabolic syndrome, hyperlipidemia, and type II diabetes. 1 The main alkaloid in the betel nut, acreoline, is toxic. It increases appetite, causes coronary artery spasm, interferes with insulin induced glucose uptake, and inhibits adiopogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its use generates euphoria 3 among users that contributes to widespread use; however, it has an array of negative effects including but not limited to oral, esophageal, and hepatocellular carcinoma, metabolic syndrome, hyperlipidemia, and type II diabetes. 1 The main alkaloid in the betel nut, acreoline, is toxic. It increases appetite, causes coronary artery spasm, interferes with insulin induced glucose uptake, and inhibits adiopogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…2 Multiple studies show high risk of diabetes, increased likelihood of coronary artery disease and all-cause mortality in betel nut users. (4,1) Specifically, Tseng's study demonstrated how, in Taiwan, increasing incidence ratios of type II diabetes with increasing age could be viewed as a dose-response relationship with betel nut chewing. 4 Reports are also available for acute toxic symptoms if betel nut is consumed in increased quantity; manifestations include palpitations, chest tightness, dyspnea, tachycardia and even MI and coma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both have been implicated as possible contributing factors for the high rates of oral disease (oral and oral-pharyngeal cancer) found in the Indian subcontinent 6 12 13. IARC has concluded that areca (or betel) nut, with or without tobacco , is carcinogenic, given the presence of areca nut-derived nitrosamines 11 14–16.…”
mentioning
confidence: 99%
“…Both products also contain high levels of toxic inorganic compounds, including heavy metals, and the use of paan has been shown to cause chromosomal dysfunction associated with the formation of oral precancerous lesions 17 18. In addition, other studies have shown that use of paan and paan masala may be related to acute cardiovascular risks, such as increases in heart rate and blood pressure, and that longer use may contribute to the onset of coronary artery disease 12 17 19…”
mentioning
confidence: 99%